极压剂的含量对化学跑合效果的研究 - 解生泽; 周超梅; 丁津原; 马先贵 (Jixie chuandong)
The effect of polyalkylbenzene sulfide and chlorcosane extreme pressure antiwear additive in aluminum grease on running performance is investigated by using BJ58A testing machine,and the collaborative running performance of polyalkylbenzene sulfide and chlorcosane extreme pressure antiwear additive is discussed.The wearing capacity variation of test piece is detailedly recorded,and the surface topography under various condition is observed by using surface profile testing instrument.The experiment result shows that extreme pressure additive content has a great influence of the process on running.The running velocity is increased greatly,the surface roughness is reduced and the running time is shortened by selecting extreme pressure additive of strength activity.